Political discourses on race and social inequalities through social media and live parliamentary debates in South Africa - Limukani Mathe (Communicare)
This article, informed by framing theory, uses qualitative content analysis to analyse the Economic Freedom Fighters’ (EFF) discourses on race and social inequalities through social media and live parliamentary debates in South Africa. The article reveals that protest and provocative political statements by EFF members attract audience and media attention, and reinforce their political agenda. Political personalities communicate their message effectively on social media and influence audiences’ perception through protestation. The well-known framing theory by the traditional mass media has been exceeded by that of social media where politicians radically engage their audiences. This paper reveals that the populist political style has much impact on social media, where political actors interact directly with audiences.